2003
DOI: 10.1046/j.1365-2125.2003.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of St John's wort with low‐dose oral contraceptive therapy: a randomized controlled trial

Abstract: Aims Breakthrough bleeding or even unwanted pregnancies have been reported in women during concomitant therapy with oral contraceptives and St John's wort extract. The aim of the present study was to investigate the effects of St John's wort extract on oral contraceptive therapy with respect to ovarian activity, breakthrough bleeding episodes and the pharmacokinetics of ethinyloestradiol and 3-ketodesogestrel. Methods Eighteen healthy females were treated with a low-dose oral contraceptive (0.02 mg ethinyloest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
49
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(52 citation statements)
references
References 31 publications
0
49
0
3
Order By: Relevance
“…This adverse event has been observed also in clinical studies (28,68,69) that have shown a higher incidence of intracyclic bleeding episodes after coadministration of SJW and oral contraceptive pills. Most importantly, reports of women becoming pregnant while using oral contraceptives and SJW have been reported by UK, German, and Swedish authorities.…”
Section: Hormonal Therapymentioning
confidence: 69%
See 1 more Smart Citation
“…This adverse event has been observed also in clinical studies (28,68,69) that have shown a higher incidence of intracyclic bleeding episodes after coadministration of SJW and oral contraceptive pills. Most importantly, reports of women becoming pregnant while using oral contraceptives and SJW have been reported by UK, German, and Swedish authorities.…”
Section: Hormonal Therapymentioning
confidence: 69%
“…It is well known that drugs inducing CYP3A4 such as rifampicin may cause reduced efficacy of oral contraceptives and breakthrough bleeding (71). Clinical studies have shown that SJW increases the clearance of oral pill components such as ethinylestradiol, norethindrone, and ketodesogestrel, and this effect is associated to breakthrough bleeding (28,68,69); interestingly, SJW extracts with low hyperforin content were found not to alter the pharmacokinetics of ethinylestradiol and 3-ketodesogestrel, the hormonal components of the oral contraceptive (45). This further highlights the concept that hyperforin is the chemical ingredient responsible of SJWinduced pharmacokinetic interactions.…”
Section: Hormonal Therapymentioning
confidence: 99%
“…Co-administration of Hypericum and oral contraceptives may increase unintended pregnancy risk [1], seven cases being reported by the United Kingdom authorities [2]. The Medical Products Agency from Sweden received eight reports of intermenstrual bleedings and one of changed menstrual bleeding from manufacturers of St John's wort products [3]; in Switzerland have been reported similar clinical cases [1].…”
mentioning
confidence: 99%
“…The Medical Products Agency from Sweden received eight reports of intermenstrual bleedings and one of changed menstrual bleeding from manufacturers of St John's wort products [3]; in Switzerland have been reported similar clinical cases [1].…”
mentioning
confidence: 99%
“…Significant decreases in the AUC were demonstrated in trials with warfarin (when administered with American ginseng) (13), midazolam (with echinacea) (14), saquinavir (with garlic) (15) and alprazolam (with ginkgo biloba) (16). In addition, St John's wort significantly decreased the AUC or C max when administered with alprazolam (AUC [17,18]), amitriptyline (AUC [19]), cyclosporin A (AUC [20]), digoxin (AUC [21,22]), fexofenadine (AUC and C max [23]), indinavir (AUC [24]), midazolam (AUC and C max [23]), omeprazole (AUC [25]), oral contraceptive (3-ketodesogestrel) (AUC [26]), simvastatin Figure 1) Sequential first-pass elimination of a theoretical drug through metabolism by the cytochrome P450 isoenzyme CYP3A4 and/or transport by P-glycoprotein (P-gp) in enterocytes of the small intestine and then hepatocytes of the liver. The percentage of the initial drug dose that is available before and after passage through the gut wall and liver is presented.…”
mentioning
confidence: 99%